Theoretical Estimation of The Influence of Plastic Deformation on Average Coefficient of Friction in the Process of Nanostructuring Burnishing of Metal Samples; Journal of Friction and Wear; Vol. 40, iss. 5 - Lyashenko Ya. A. Yakov Aleksandrovich (2019, 2019)
Title screen